PELABELAN FUZZY PADA GRAF - Siti Rahmah Nurshiami; Suroto Suroto; Fajar Hoeruddin (Universitas Jenderal Soedirman, 2014)
This paper discusses fuzzy labeling graph and its properties. The properties discussed are fuzzy labeling subgraph, union graph, and fuzzy magic graph. The results showed that the strength of connectedness for pair of vertices in a graph with fuzzy labeling is always greater than or equal to the strength of connectedness for pair of vertices in its subgraph. In addition, union of two graph with fuzzy labeling will form a graph with fuzzy labeling. Meanwhile, on magic labeling there is always a fuzzy bridge on fuzzy magic graph.